Heat-shrinkable low and medium voltage moulded shapes. Specification for individual materials. Sheet 102: Heat-shrinkable, polyolefin, anti-tracking moulded shapes for medium voltage applications Part 3-102, (24th April 2018) - British Standards Institution,
No abstract available